NKG2C+NKG2A− Natural Killer Cells are Associated with a Lower Viral Set Point and may Predict Disease Progression in Individuals with Primary HIV Infection - Ma, Meichen; Wang, Zhuo; Chen, Xi; Tao, Anfu; He, Lei; Fu, Shuai; Zhang, Zining; Fu, Yajing; Guo, Chenxi; Liu, Jing; Han, Xiaoxu; Xu, Junjie; et al. (Frontiers in Immunology, 2017)
NK cells are the first line of defense against pathogens of the immune system and also play an important role in resistance against HIV. The activating receptor NKG2C and the inhibitory receptor NKG2A co-modulate the function of NK cells by recognizing the same ligand, HLA-E. However, the role of NKG2Aand NKG2C on viral set point and the prediction of HIV disease progression have been rarely reported. In the present study, we determined the expression of NKG2C or NKG2A on the surface of NK cells from 22 individuals with primary stage HIV infection (PHI) and 23 HIV-negative normal control subjects (NC). The CD4+ T cell count and plasma level of HIV RNA in the infected individuals were longitudinally followed-up for about 720 days. The proportion of NKG2C+NKG2A- NK cells was higher in subjects from the low set point group and was negatively correlated with the viral load. In addition, strong anti-HIV activities were observed in NKG2C+NK cells from the HIV-positive donors. Furthermore, a proportion of NKG2C+NKG2A- NK cells> 35.45%, and a ratio of NKG2C/NKG2A > 1.7 were predictive for higher CD4+T cell counts 720 days after infection. Collectively, the experimental results allow us to draw the conclusion that NKG2C+ NK cells might exert an antiviral effect and that the proportion of NKG2C+NKG2A- NK cells, and the ratio of NKG2C/NKG2A, are potential biomarkers for predicting HIV disease progression.